2022
DOI: 10.3390/antibiotics11020230
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Prophylaxis Reduces the Rate of Surgical Site Infection in Upper Gastrointestinal Surgery: A Systematic Review

Abstract: Surgical site infection occurs with high frequency in gastrointestinal surgery, contributing to the high incidence of morbidity and mortality. The accepted practice worldwide for the prevention of surgical site infection is providing single- or multiple-dose antimicrobial prophylaxis. However, most suitable antibiotic and optimal duration of prophylaxis are still debated. The aim of the systematic review is to assess the efficacy of antimicrobial prophylaxis in controlling surgical site infection rate followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 76 publications
1
16
0
Order By: Relevance
“…More extended lymphadenectomy should only be performed in dedicated highvolume hospitals, due to the high risk of post-operative complications and mortality [60].…”
Section: D2 Plus and D3 Lymphadenectomiesmentioning
confidence: 99%
“…More extended lymphadenectomy should only be performed in dedicated highvolume hospitals, due to the high risk of post-operative complications and mortality [60].…”
Section: D2 Plus and D3 Lymphadenectomiesmentioning
confidence: 99%
“…Marano et al reported that using antimicrobials such as cefazolin and cefuroxime during esophagogastric surgery to reduce infections within the intraoperative period should not exceed two antimicrobial agents, at the lowest efficacious and safe doses to avoid the emergence of multi-drug resistance [ 53 ]. They reported that further studies are needed to investigate the optimal antimicrobial regimen in esophageal surgery [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Marano et al reported that using antimicrobials such as cefazolin and cefuroxime during esophagogastric surgery to reduce infections within the intraoperative period should not exceed two antimicrobial agents, at the lowest efficacious and safe doses to avoid the emergence of multi-drug resistance [ 53 ]. They reported that further studies are needed to investigate the optimal antimicrobial regimen in esophageal surgery [ 53 ]. Ruol et al stated that a single-dose prophylactic regimen provides adequate prophylaxis and significant cost-savings in comparison with multiple-dose prophylactic regimens in patients undergoing major surgery for esophageal cancer [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The THD is a safe and effective atraumatic technique associated, not influencing sphincter complex or anal function, with the best short-term clinical and surgical outcomes (rapid symptoms relief, lesser surgical site infection ( 53 ) and postoperative complications). Fast postoperative recovery, early discharge, and quickly return to normal daily activities and works substantially improves patient's QoL ( 54 ).…”
Section: Discussionmentioning
confidence: 99%